Analisis Algoritma K-Means Clustering Untuk Menentukan Strategi Promosi Penjualan Sepeda Motor Studi Kasus PT. Alfa Scorpii - Abdul Muni (JUTI UNISI, 2020)
PT. Alpa Scorpii is the sector private the economy in the motorcycle sales. The utilization of the data is not maximum, sales report that is used only limited to report. Promotion strategy is to increase the income of the company in relation to the straight way with the cost. The data mining so that data can be used as the existing knowledge from the large data sets or with the term knowledge discovery or pattern recognition. Many methods in data mining one only with the method the algorithm K-Means the Cluster. Clustering data so that the field of marketing can perform the motor sales promotion strategy to new customers with the right and can improve corporate earnings.